2018
DOI: 10.1021/acs.jmedchem.8b00653
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Strategy for Lead Optimization Based on Fragment Growing: The Diversity-Oriented-Target-Focused-Synthesis Approach

Abstract: Over the past few decades, hit identification has been greatly facilitated by advances in high-throughput and fragment-based screenings. One major hurdle remaining in drug discovery is process automation of hit-to-lead (H2L) optimization. Here, we report a time- and cost-efficient integrated strategy for H2L optimization as well as a partially automated design of potent chemical probes consisting of a focused-chemical-library design and virtual screening coupled with robotic diversity-oriented de novo synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 56 publications
(102 reference statements)
2
68
0
1
Order By: Relevance
“…In this case being the most populated in the MD with amentoflavone. Also, the presence of water bridges with this residue proved significant, a feature recently observed by other groups [66]. Furthermore, this residue is present only on the BRD4 BD1, providing specific contact with histone H3 via hydrogen bonding, an interaction not present with inhibitors such as JQ-1 [69].…”
Section: Molecular Dynamicssupporting
confidence: 55%
See 1 more Smart Citation
“…In this case being the most populated in the MD with amentoflavone. Also, the presence of water bridges with this residue proved significant, a feature recently observed by other groups [66]. Furthermore, this residue is present only on the BRD4 BD1, providing specific contact with histone H3 via hydrogen bonding, an interaction not present with inhibitors such as JQ-1 [69].…”
Section: Molecular Dynamicssupporting
confidence: 55%
“…An example of this is Asp145, a contact with amentoflavone with a rather small population. However, this contact has been identified as significant, as it provides ligand stabilization and water network interaction [66].…”
mentioning
confidence: 99%
“…When selecting candidates for prospective evaluation, we found that some of the molecules required complicated synthesis. Incorporating into our pipeline a strategy such as DOTS 33,48 , other retrosynthesis algorithms [49][50][51] or even the use of synthetic feasibility scores [52][53][54] , can significantly improve the quality of proposed candidates in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the problem that SAR by catalog has the limitation to cover only the finite chemical space of commercially available compounds (Hoffer et al, 2018), it is possible to FIGURE 5 | Example of a hot spot analysis using FTMap web server of the oncogenic B-RAF kinase, the target of the first marketed drug from fragment-based drug design, vemurafenib. The surface of the binding site is depicted in gray.…”
Section: Molecular Dockingmentioning
confidence: 99%